2020
DOI: 10.21873/invivo.11924
|View full text |Cite
|
Sign up to set email alerts
|

Vestiges of Ossified Spheno-occipital Suture in an Elderly Patient With Down Syndrome and Lateral Skull Base Fracture

Abstract: Background/Aim: Down syndrome (DS) patients often show characteristic changes in the skull, e.g. short cranial base. The synchondroses of the skull base have a significant influence on the shape of the skull. The sphenooccipital synchondrosis (SOS) is the last of the basal synchondroses to ossify. This report is about residual ossification of SOS in an elderly patient with DS. Case Report: The 65-year-old DS patient was polytraumatized by a fall. In the course of treatment, a purulent otitis externa on the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Okamoto et al (1996) noted a white line at the site in a 62‐year‐old woman. Similarly, Friedrich et al (2020) reported a pair of radio‐opaque lamellae at the same position in a 65‐year‐old man with Down syndrome. In contrast, Adem et al (1999) noted an incompletely fused spheno‐occipital synchondrosis in a 30‐year‐old man.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Okamoto et al (1996) noted a white line at the site in a 62‐year‐old woman. Similarly, Friedrich et al (2020) reported a pair of radio‐opaque lamellae at the same position in a 65‐year‐old man with Down syndrome. In contrast, Adem et al (1999) noted an incompletely fused spheno‐occipital synchondrosis in a 30‐year‐old man.…”
Section: Discussionmentioning
confidence: 81%
“…Shirley and Jantz (2011) stated that a fusion scar can persist for decades, but they were referring to a shallow linear groove on the underside of an isolated skull. In terms of how long the fusion line can persist, however, the evidence of Okamoto et al (1996), McKinney (2017) and Friedrich et al (2020) cited earlier indicates that it can remain long after the synchondrosis closes and thus does not indicate recent closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation